Acute effect of different doses of caffeinated chewing gum on exercise performance in caffeine-habituated male soccer players - Yildirim, Ulas Can; Akcay, Neslihan; Alexe, Dan Iulian; Esen, Ozcan; Gulu, Mehmet; Cîrtiţă-Buzoianu, Cristina; Cinarli, Fahri Safa; Cojocaru, Marilena; Sari, Cengizhan; Alexe, Cristina Ioana; Karayigit, Raci (Frontiers in Nutrition, 2023)
The ergogenic benefits of caffeine have been well established, but there is scarce research on its chewing gum form. The present research aimed to examine the effects of different doses (100 and 200 mg) of caffeinated chewing gum on muscle strength, vertical jump performance, and ball-kicking speed in trained male soccer players. In a double-blind, randomized counterbalanced, and crossover research design, 14 male soccer players (age = 22 ± 2 y; body mass = 74.2 ± 7.1 kg; height = 180.0 ± 6.8 cm; habitual caffeine intake = 358.9 ± 292.4 mg/day) participated in three experimental trials. In each trial, participants performed isometric handgrip strength, quadriceps and hamstring strength, ball-kicking speed, and 15 s countermovement jump test 10 min after chewing 100 mg (LCAF) or 200 mg (MCAF) of caffeinated gum or placebo (PLA). MCAF improved quadriceps strength (53.77 ± 5.77 kg) compared to LCAF (49.62 ± 8.81 kg, p = 0.048) and PLA (49.20 ± 7.20 kg, p = 0.032). However, neither LCAF nor MCAF had a significant effect on the isometric handgrip and hamstring strength, ball-kicking speed, and 15 s countermovement jump test (all p > 0.05). These findings support chewing gum as an alternative mode of caffeine administration which can be used as a nutritional ergogenic aid for trained soccer players, at least for quadriceps strength.